2018
DOI: 10.1021/acs.langmuir.8b01554
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium-Based Ionic Liquids Affect Morphology and Rigidity of Living Cells: An Atomic Force Microscopy Study

Abstract: The study of the toxicity, biocompatibility, and environmental sustainability of room-temperature ionic liquids (ILs) is still in its infancy. Understanding the impact of ILs on living organisms, especially from the aquatic ecosystem, is urgent, since large amounts of these substances are starting to be employed as solvents in industrial chemical processes, and on the other side, evidence of toxic effects of ILs on microorganisms and single cells have been observed. To date, the toxicity of ILs has been invest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 105 publications
2
31
0
Order By: Relevance
“…5 ). The reduction correlates positively with the length of the imidazolium IL-cation tail and has been associated to the ability of the ILs to alter the membrane-actin cytoskeleton wall (Galluzzi et al 2018 ). A drop in the in-plane elasticity of the cellular lipid membrane has been measured in the human liver cancer cell line Huh7.5 incubated in [C 10 mim][BF 4 ], and has been associated to the rearrangement of lipids due to the presence of the ILs in the lipid region.…”
Section: Mechanisms Of Action Of Ilsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 ). The reduction correlates positively with the length of the imidazolium IL-cation tail and has been associated to the ability of the ILs to alter the membrane-actin cytoskeleton wall (Galluzzi et al 2018 ). A drop in the in-plane elasticity of the cellular lipid membrane has been measured in the human liver cancer cell line Huh7.5 incubated in [C 10 mim][BF 4 ], and has been associated to the rearrangement of lipids due to the presence of the ILs in the lipid region.…”
Section: Mechanisms Of Action Of Ilsmentioning
confidence: 99%
“…5 AFM scan of the local elastic modulus of osteoblast cells a before and b after the addition of [C 4 mim][Cl] at 0.1 M concentration, showing the overall reduction of the cell membrane elasticity and the destabilization of the cytoskeleton motif induced by the IL (Benedetto and Ballone 2018a ). In c and d , Young’s modulus mean values ± errors for MDA-MB-231 cells interacting with different concentration of [C 4 mim][Cl] and [C 8 mim][Cl], respectively (Galluzzi et al 2018 ). Figures reproduced with permission from the publisher
Fig.
…”
Section: Mechanisms Of Action Of Ilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing interest in implementing ionic liquids (ILs, a class of compounds composed of organic cations and inorganic anions) [1] in a broad range of medicinal and biotechnological applications, such as drug synthesis, fabrication of drug delivery systems, utilization as active pharmaceutical ingredients as well as chemical biosensors, [2,3] makes it desirable to conduct fundamental research to unveil the interaction between surface-active ionic liquids (SAILs) with fatty acids and phospholipids with an ultimate goal of understanding their impact on the structure and dynamics of biological membranes. [4][5][6][7] The synthesis, self-assembly, and interfacial properties of a series of 1-alkyl-3-methylimidazolium based ILs ([C n -mim]X, Scheme 1A) have been investigated independently by several research groups using various approaches. [8][9][10][11][12][13][14][15][16][17][18][19] Blesic et al reported on the micellization of [C n -mim]Cl, where the formation of aggregates was observed when n > 8.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of apoptosis is an important feature of tumor cells [22,23]. Singh (2019) has shown that the apoptosis level of colorectal cancer and adenoma is significantly reduced [24].…”
Section: Scs Induces Apoptosismentioning
confidence: 99%